Ethical and social recognition of participation in drug clinical trials: French public views on financial compensation for participants - Laure Peyro-Saint-Paul; Cathy Gaillard; Célia Berchi; Clément Gakuba; Charlotte Gourio; Guillaume Grandazzi; Michael Joubert; Sylvie Brucato; Clémence Bechade; Rémy Morello (PLOS One, 2026)
Background Drug clinical trial participants should be fairly compensated for inconvenience while avoiding undue inducement. However, European regulations provide limited operational guidance on when compensation should be offered and how it should be determined. The INDEM3 project aims to develop a decision-support tool for sponsors and ethics committees, beginning with an assessment of exploratory public perspectives in France. Methods An exploratory population-based survey was conducted using a self-administered questionnaire with an estimated completion time of approximately seven minutes. A minimum of 60 individuals was targeted, with or without chronic condition or prior research experience. The questionnaire assessed general views on financial compensation and responses to three fictional drug clinical trial scenarios varying in risk, burden, and direct benefit. Distribution occurred in healthcare settings and via social networks. Results Between March 2024 and January 2025, 65 responses were collected. Most respondents (75%) supported financial compensation for participation in drug clinical trials. The most frequently cited criteria were exposure to a new investigational drug (65%), invasive procedures (63%) and experiencing income lost (63%), and absence of direct personal benefit (28%). For the scenarios, the proportion of respondents supporting compensation and the median proposed amounts were as follows: Scenario 1 (no direct benefit, high burden, low uncertainty): 81%; €300 [€140–300]. Scenario 2 (some direct benefit, low burden, moderate uncertainty): 48%; €150 [€100–200]. Scenario 3 (some direct benefit, high burden and high uncertainty): 60%; €500 [€200–1,000]. Conclusion Respondents in this exploratory French survey largely supported financial compensation for participation in drug clinical trials. Compensation is perceived as a proportionate ethical and social recognition of uncertainty, burden and lack of direct benefit. These findings provide an empirical basis for developing transparent tools to guide compensation decisions.